2013
DOI: 10.1155/2013/764812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flow-Induced Dynamic Stress and Vibration of Volute Casing for a Large-Scale Double-Suction Centrifugal Pump

Abstract: The transient analysis was carried out to investigate the dynamic stress and vibration of volute casing for a large double-suction centrifugal pump by using the transient fluid-structure interaction theory. The flow pulsations at flow rate ranging from 60% to 100% of the nominal flow rate ( ) were taken as the boundary conditions for FEM analysis of the pump volute casing structure. The results revealed that, for all operating conditions, the maximum stress located at the volute tongue region, whereas the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Wang [6] carried out the transient analysis to investigate the dynamic stress and vibration of volute casing for a large double-suction centrifugal pump by using the transient fluid-structure interaction theory. The results revealed that, for all operating conditions, the maximum stress located at the volute tongue region, whereas the maximum vibration displacement happened close to the shaft hole region, and the blade passing frequency and its harmonics were dominant in the variations of dynamic stress and vibration displacement.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Wang [6] carried out the transient analysis to investigate the dynamic stress and vibration of volute casing for a large double-suction centrifugal pump by using the transient fluid-structure interaction theory. The results revealed that, for all operating conditions, the maximum stress located at the volute tongue region, whereas the maximum vibration displacement happened close to the shaft hole region, and the blade passing frequency and its harmonics were dominant in the variations of dynamic stress and vibration displacement.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Due to the back-to-back arrangement of the twin impellers, the average axial force in double-suction pumps is zero. However, these pumps usually involve high energies and suffer from more complex pressure fluctuations than other centrifugal pumps [1,2]. The inlet fluid is separated by the two suctions and flows into impellers, where the two fluids are independent of each other.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the sound pressure effect on the structure of the centrifugal pump was not significant. Wang et al 13 studied the vibration and dynamic stress of volute casting for a centrifugal pump, based on the transient fluid-structure interaction theory.…”
Section: Introductionmentioning
confidence: 99%